Fundamental of Entrepreneurship ENT 300 : Bahulu's Ala Carte / Muhammad Faiz Masnan... [et al.] - Yusof, Mohamad Agus; Ramlan, Mohamad Hariff; Hud, Aslahuddin Azwan; Suhaimi, Hafizan; Litor, Ivan Walter (2015)
Bahulu's Ala Carte is the most popular bahulu in our company. Bahulu's Ala Carte with tagline "Sedap Baitu Kuih Bahulu" which located at located at Kota Kinabalu, with address: Bahulu's Ala Carte Enterprise, Centre Point Sabah, Mo 1 Centre Point Sabah, 88000 Kota Kinabalu, Sabah. Bahulu's Ala Carte is our company in which targeted on food production in Malaysia, especially Sabah. Differences in size and shape make this cake looks interesting and suitable to serve for any occasion. Most people in Malaysia like the light and dry texture that gives an opportunity to this cake to be one of marketable product as people love simple things especially food.